Neuromodulatory effect of plant metabolites (Sciences of Phytochemistry, 2022)
Neurological disorders (NDDs) are diseases that affect the central and peripheral nervous systems. Gradual malfunction and destruction of the neurons or the nerve cells characterize them. Every year, NDDs affect millions of people worldwide. Over the years, several neuromodulatory techniques have been introduced to improve the quality of life for those affected by NDDs. NDDs are chronic and incurable conditions, however, bioactive substances derived from medicinal plants have emerged as the greatest choice for their prevention and treatment. Literature evidences several benefits of plant metabolites as alternative medicines for the prevention and treatment of NDDs. Numerous investigations have shown plant metabolites to possess beneficial biological effects because of their qualities, which include but are not limited to anti-inflammatory, antioxidant, and neuroprotective actions. Practices of folk medicine and several studies have also guided many phytopharmacological interventions toward the treatment of NDDs. This review aims to highlight secondary metabolites (alkaloids, flavonoids, steroids, terpenoids) of plants with neuroprotective action that could potentially play an important role in the prevention and management of NDDs.